Multiple interventions to strengthen immunization services in an Angolan district. (13th November 2019) - Fattorini, M; Raguzzoni, G; Cuccaro, C; Nante, N; Quercioli, C; Ndilimondjo, J M N; Caresia, C; Putoto, G
Abstract: Background: Immunization represents one of the most effective intervention in public health. In the Sustainable Development Goals era, adequate vaccination services are still crucial for the prevention of infectious diseases and the reduction of under-5 mortality. However, in 2017 WHO estimated that children <1 year who did not receive the third dose of Diphtheria-Tetanus-Pertussis (DTP3) vaccine were 19.2 million globally, and 600000 of these were located in Angola, a Sub-Saharan country with an estimated DTP3 coverage of 52%. Since 2000, Italian Non-Governmental Organization (NGO) Doctors with Africa CUAMM supports the activity of the hospital of Chiulo in the commune of Mucope (district of Ombadja, south of Angola). Aim of the study is to describe the interventions implemented to strengthen the immunization services performed by the hospital Public Health Staff (PHS). Methods: In May 2018 the NGO started to implement multiple interventions to enhance the number of vaccine doses administered. Firstly, outreach immunization sessions were reorganized and reinforced, for example involving local Community Health Workers in the identification of villages with a high burden of unvaccinated children. Other actions were the continuous training of the PHS in data collection and the increased collaboration with the Ombadja District Health Department in order to develop a more efficient vaccine supply chain at local level. Results: In 2018, among children <1 year the PHS administered 19746 doses, with a 22.3% growth compared to 2017 (15349 doses). Doses administered during outreach sessions increased by 35.4% (6597 versus 4259 doses). Estimated DTP3 coverage in Mucope commune was 71% (2017, 59%). Conclusions: The WHO "Reaching Every Community" strategy emphasizes the importance of high quality immunization services in hard-to-reach areas. The organisation of well-functioning immunization services requires a multifaceted approach by the involved stakeholders. Key messages: In 2017, globally 19.2 million of children <1 year did not receive the recommended three DTP doses. Six-hundred thousand were located in Angola. To obtain and sustain an adequate vaccination coverage, especially in hard-to-reach areas, multiple and well-coordinated actions should be implemented by all the involved stakeholders.